Incidence and predictors of opportunistic infections in adolescents and adults after the initiation of antiretroviral therapy: A 10-year retrospective cohort study in Ethiopia - Woldegeorgis, Beshada Zerfu; Diro, Chala Wegi; Yohannes, Bereket; Kerbo, Amene Abebe; Asgedom, Yordanos Sisay (Frontiers in Public Health, 2022)
Background: Opportunistic infections (OIs) are the leading cause of morbidity and mortality in people living with the human immunodeficiency virus (PLHIV). However, there are few robust recent data on the rates of OIs and the risk factors that contribute to their occurrence. Therefore, the current study sought to determine the incidence of OIs and identify predictors among adolescents and adults after the initiation of antiretroviral therapy (ART) at Wolaita Sodo University Comprehensive Specialized Hospital (WSUCSH), Southern Ethiopia. Methods: A retrospective cohort study design was employed. The study population was adults who initiated ART between 1 January 2012 and 31st December 2021. A simple random sampling technique was used to select 537 patients' records. We reviewed the medical records of the sampled individuals from May 1 to June 15, 2022. Kobocollect version 2021.2.4 and STATA version 14.0 software were used for data collection and analysis, respectively. We calculated the incidence rate per 100 person-years of observation (PYO) with 95% confidence intervals (CI). The Weibull regression model was fitted after the goodness of fit test for the Cox proportional hazard model was deemed inadequate. An adjusted hazard ratio (AHR) with 95% CI was used to identify a significant predictor of OIs.The statistical decision was made at a 5% significance level. Results: A total of 515 participants contributed to 1829 person-years of risk, of whom 164 (31.84%) exhibited at least one OI. The overall incidence rate of OIs was 8.97 cases (95% CI: 7.69, 10.44) per 100 PYO. Being female [AHR: 1.65 (95% CI (1.15, 2.36), P=0.007)], World Health Organization(WHO) HIV clinical stage III [AHR: 1.98 (95% CI (1.12,3.51), P=0.019)], individuals who didn’t take cotrimoxazole preventive therapy(CPT) [AHR: 2.58 (95% CI (1.62, 4.11), P< 0.001)], mild malnutrition [AHR: 1.62(95% CI (1.06, 2.54), P=0.035)], and poor adherence to ART [AHR: 4.21 (95% CI (2.39, 7.44), P <0.001)] were independent predictors of OIs. Conclusions: The rate of OIs after the initiation of ART was still high. Moreover, being female, not taking CPT, poor adherence to ART, mild malnutrition, and advanced HIV disease at presentation were found to increase the hazards of developing OIs .